Magnetic Resonance Elastography Shear Wave Velocity Correlates with Liver Fibrosis and Hepatic Venous Pressure Gradient in Adults with Advanced Liver Disease. (5th April 2017) - Gharib, Ahmed M.; Han, Ma Ai Thanda; Meissner, Eric G.; Kleiner, David E.; Zhao, Xiongce; McLaughlin, Mary; Matthews, Lindsay; Rizvi, Bisharah; Abd-Elmoniem, Khaled Z.; Sinkus, Ralph; Levy, Elliot; Koh, Christopher; et al.
Abstract : Background. Portal hypertension, an elevation in the hepatic venous pressure gradient (HVPG), can be used to monitor disease progression and response to therapy in cirrhosis. Since obtaining HVPG measurements is invasive, reliable noninvasive methods of assessing portal hypertension are needed. Methods. Noninvasive markers of fibrosis, including magnetic resonance elastography (MRE) shear wave velocity, were correlated with histologic fibrosis and HVPG measurements in hepatitis C (HCV) and/or HIV-infected patients with advanced liver disease enrolled in a clinical trial of treatment with simtuzumab, an anti-LOXL2 antibody. Results. This exploratory analysis includes 23 subjects: 9 with HCV monoinfection, 9 with HIV and HCV, and 5 with HIV and nonalcoholic steatohepatitis. Median Ishak fibrosis score was 4 (range 1–6); 11 subjects (48%) had cirrhosis. Median HVPG was 6 mmHg (range 3–16). Liver stiffness measured by MRE correlated with HVPG (r = 0.64, p = 0.01 ), histologic fibrosis score (r = 0.71, p = 0.004 ), noninvasive fibrosis indices, including APRI (r = 0.81, p < 0.001 ), and soluble LOXL2 (r = 0.82, p = 0.001 ). On stepwise multivariate regression analysis, MRE was the only variable independently associated with HVPG (R 2 = 0.377, p = 0.02 ). Conclusions. MRE of the liver correlated independently with HVPG. MRE is a valid noninvasive measure of liver disease severity and may prove to be a useful tool for noninvasive portal hypertension assessment. Trial Registration Number . This trial is registered with NCT01707472 .